Praktik urban farming berbasis pemanfaatan limbah organik rumah tangga untuk mewujudkan rumah pangan lestari - Irianto; Puji Lestari, Ardiyaningsih; Ermadani, Ermadani; Alia, Yulia; Kartika, Elis (Proceedings Academic Universitas Jambi, 2025)
Urban farming refers to agricultural activities conducted in urban areas. This practice has developed in response to the decreasing availability of agricultural land, while the population continues to grow. Therefore, urban farming serves as a strategic solution for the productive utilization of limited land in cities. The objective of this community service program is to enhance community knowledge and skills in urban farming practices, thereby contributing to household food security. The program was implemented using the Participatory Rural Appraisal approach, which actively involved the community at every stage of the activity. The participants were mothers who are members of the Family Empowerment and Welfare group in Sungai Putri Village, Danau Sipin District, Jambi City. The main focus of the activity was the utilization of household organic waste, which was processed into solid compost and liquid organic fertilizer for crop cultivation. To achieve the objectives of urban farming effectively, several aspects were considered, including the selection of plant species with high nutritional and economic value that can be harvested continuously. The selected crops were pak-choi, Talinum paniculatum, and chili, cultivated both hydroponically and in polybags. The success of the program was demonstrated by the high level of community participation, with attendance reaching 90%, as well as by the improvement in participants’ understanding of urban farming, as reflected in the increase of average pre-test scores (42) to post-test scores (77). These results indicate a significant improvement in community knowledge and skills through outreach and mentoring activities.